Leading in the certainty of uncertain times - Wynen, Susan E. van (HTS teologiese studies, 2020)
This research focused on the potential for Christ-following leaders to develop a theological and missiological posture in response to the current volatile, uncertain, complex and ambiguous (VUCA) world context. This research looks at how the attitudes and actions of the corporate world have influenced those of Christian organisations and Christian leadership. The corporate world primarily focuses on strategies for overcoming the challenges of the VUCA environment, but this research explores how Christ-following leaders might benefit from looking more deeply at what VUCA represents, rather than merely accepting and reacting to it. The research used a literature review to develop the groundwork for an increased understanding of how God and VUCA relate and how Christ followers can develop a perspective in keeping with an understanding of God’s mission, their calling and the VUCA world mindset. Although some research has been done regarding spirituality as part of a response to the VUCA world, it has often focused on the outward expressions (morality, values, collaboration and service) with little attention to the Christ follower’s source of spiritual life, the trinitarian God. This research integrates recognition of the character of God, evaluation of VUCA realities and rhetoric, and the responsibilities and opportunities of leaders who desire to participate in God’s mission. In this process, the research explores strategy metaphors, missional thinking and leadership implications.Contribution: This research encourages greater theological and missiological exploration of the Christian leader’s posture and response to the VUCA world mindset. The research engages with corporate thinking regarding strategy and the implications of VUCA and with theological and missiological thinking regarding God’s role, the leader’s role and the nature of current contexts, both local and global.